2019
DOI: 10.1002/hep4.1313
|View full text |Cite
|
Sign up to set email alerts
|

High‐Quality Diets Are Associated With Reduced Risk of Hepatocellular Carcinoma and Chronic Liver Disease: The Multiethnic Cohort

Abstract: Hepatocellular carcinoma (HCC) and chronic liver disease (CLD) are major sources of morbidity and mortality globally. Both HCC incidence and CLD mortality are known to vary by race. There is limited research on the association between dietary measures and these outcomes in a diverse population. We prospectively investigated the associations between four diet quality index (DQI) scores (Healthy Eating Index‐2010, Alternative Healthy Eating Index‐2010, Alternate Mediterranean Diet [aMED], and Dietary Approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 34 publications
9
33
0
Order By: Relevance
“…9 A second study suggested that closer adherence to a high-quality diet, assessed by the HEI-2010, aHEI-2010, aMED and DASH, was related to a reduction in CLD mortality. 12 Our study extends the study to HEI and HCC mortality. In contrast to the previous studies, we only observed a suggestive, nonsignificant, inverse association between HEI-2015 scores and HCC mortality.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…9 A second study suggested that closer adherence to a high-quality diet, assessed by the HEI-2010, aHEI-2010, aMED and DASH, was related to a reduction in CLD mortality. 12 Our study extends the study to HEI and HCC mortality. In contrast to the previous studies, we only observed a suggestive, nonsignificant, inverse association between HEI-2015 scores and HCC mortality.…”
Section: Discussionsupporting
confidence: 54%
“…The studies observed that adhering to healthy dietary patterns reduced the risk of developing HCC in diverse populations. [9][10][11][12][13][14][15] However, to date, few studies have investigated whether adherence to a healthy diet could improve the prognosis of HCC. Nevertheless, adherence to dietary recommendations has been reported to be associated with a lower risk of dying from chronic liver disease (CLD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-six studies were eligible for full text screening and 46 of these were excluded for the following reasons: abstract only ( n = 11), included only one nutrient ( n = 9), wrong article type or study design ( n = 4), too broad such as studying overall lifestyle habits rather than a focus on diet ( n = 16), looking at MAFLD not HCC ( n = 1) and looking at serum/biomarkers ( n = 5). There were 30 observational studies included in the systematic review [ 4 , 7 , 10 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data extracted from the included 30 articles are presented in Table 3 . All studies were observational and of these: seventeen were cohort, [ 20 , 21 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 38 , 41 , 42 , 43 , 44 , 45 ]; seven were case–control, [ 4 , 14 , 23 , 33 , 37 , 39 , 40 ] and six were cohort with nested case–control subset [ 7 , 10 , 24 , 25 , 26 , 36 ]. In total the 30 studies included 5,222,534 participants aged between 25–85 years across 22 countries including Asian, American and European populations.…”
Section: Resultsmentioning
confidence: 99%